(untitled) (Hematology Meeting Reports, 2009)
Both diffuse large B-cell lymphoma (DLBCL) and mantle cell lymphoma (MCL) remain major therapeutic challenges in spite of the recent improvements conferred by the addition of the anti-CD20 monoclonal antibody rituximab to chemotherapy. Radioimmunotherapy (RIT) which enhances the efficacy of anti-CD20 immunotherapy by taking advantage of the high radiosensitivity of lymphoma cells is an option to improve outcome. Encouraging results with 90Y-ibritumomab tiuxetan as a single agent have been reported in relapsed/refractory DLBCL and MCL. However, in light of the constantly increasing clinical experience with RIT, clinicians face the challenge of how to best integrate this promising new treatment option into existing established treatment algorithms. Preliminary results with 90Y-ibritumomab tiuxetan as a consolidation treatment following first-line immunochemotherapy are promising. By incorporating the most recent data in this rapidly developing field, this review article serves to define the potential role of 90Y-ibritumomab tiuxetan in the overall management of DLBCL and MCL patients not eligible for transplantation.